Analisis Peran Bahasa Indonesia dan Bahasa Madura dalam Meningkatkan Efektivitas UKM dan Interaksi Sosial Masyarakat Kecamatan Tanah Merah - Nur Lailatul Fajriyah; Nurkholis Biraly Utomo; Belda Evelyna Kris; Bima Kurniawan (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to describe the patterns of Indonesian and Madurese language use, identify the factors influencing language choice, and analyze the role of both languages in enhancing the effectiveness of Micro, Small, and Medium Enterprises (MSMEs) and social interaction among the community in Tanah Merah District, Bangkalan. The research employed a qualitative descriptive method with an ethnographic case study design and discourse analysis. Data were collected through direct observation at Tanah Merah Market, in-depth interviews with MSME actors, and documentation in the form of photographs and interview recordings. The findings reveal that Madurese dominates daily communication because it fosters closeness and trust with local customers, while Indonesian functions as a lingua franca when interacting with buyers from outside Madura. Code-switching between the two languages proved to be an adaptive communication strategy primarily motivated by the need for social capital maintenance rather than market expansion alone. The implications of this study confirm that bilingual competence constitutes both an economically and socially valuable communicative asset for MSME actors in multiethnic regions, warranting greater attention in MSME development programs by relevant stakeholders.